Metallurgical modelling of welding - Grong, Øystein (Institute of Materials, 1997)
Metallurgical Modelling of Welding gives graduate students, engineers and researchers an in-depth insight into the field of welding metallurgy, providing a broad overview of its fundamental principles. In recent years, significant progress has been made in the understanding of the chemical and physical processes which take place during weldning. This book brings together all the basic components to reach the goal of faster process development, optimisation of processes and properties, and the possibility of developing new and weldable alloys. The second edition includes a new chapter of exercis.
Keywords: Welding.; Welding -- Mathematical models.; Physical metallurgy.; Alloys -- Metallurgy.; elektronické knihy; electronic books